The Ebola Epidemic and Cholera Outbreak and The International Response - Richard B. Roberts (Medicine, Law & Society, 2017)
Infectious diseases are responsible for 15 million of the 57 million deaths worldwide despite the remarkable discoveries of antibiotics and vaccines. Many individuals succumb to microbial diseases in poor and less-developed countries where these preventive and therapeutic modalities are not available. Furthermore these less fortunate countries do not have the resources or public health infrastructure to combat unforeseen and explosive outbreaks. Two relatively recent outbreaks are reviewed in this article; the Ebola epidemic in West Africa and the cholera outbreak in Haiti. This outbreak of cholera, in a country of only 7.8 million inhabitants, is one of the largest ever recorded worldwide. Early intervention by international health organizations is critical to curtail and ultimately control infectious disease outbreaks and epidemics. This responsibility, especially for less-developed countries, lies in the hands of the United Nations and World Health Organization. Unfortunately, the international response from the UN and WHO was slow, cumbersome and poorly coordinated both in West Africa and Haiti.